2015
DOI: 10.18805/ijare.v49i5.5803
|View full text |Cite
|
Sign up to set email alerts
|

Improving use efficiency of applied phosphorus fertilizer by zinc fertilization in <italic>Basmati</italic> rice-wheat cropping system

Abstract: Rice-wheat rotation is the most important cropping system of the Indo-Gangetic plains. On-farm experiment was conducted to reveal the effect of Zn fertilization on yield, uptake of nutrient, utilization efficiency (UE) and grain output per unit of fertilizer use through agronomic efficiency (AE) of P and Zn in rice-wheat rotation. The experiment was conducted with rice (cv. Pusa Basmati 1) and wheat (cv. UP-2425) by imposing twelve treatments involving four different doses of P (0, 20, 40 and 60 kg P 2 O 5 ha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…However, PFP p showed the decreasing trends when P was applied with Zn, as P and Zn have antagonist effect on plant growth, which resulted in poor recovery of P [49]. In this study we have found that the PFP of applied P either alone or in combination with N and K was considerably higher in rice crop as compared to the wheat crop across the locations having different water regimes in contrary to the earlier reports that rice respond poorly to phosphorus as compared to wheat in RWCS [7,50]. This indicates that at farmer's field rice is more responsive to N and P application as farmers of the selected locations uses the readily soluble SSP as a source of phosphatic fertilizer.…”
Section: Discussioncontrasting
confidence: 87%
“…However, PFP p showed the decreasing trends when P was applied with Zn, as P and Zn have antagonist effect on plant growth, which resulted in poor recovery of P [49]. In this study we have found that the PFP of applied P either alone or in combination with N and K was considerably higher in rice crop as compared to the wheat crop across the locations having different water regimes in contrary to the earlier reports that rice respond poorly to phosphorus as compared to wheat in RWCS [7,50]. This indicates that at farmer's field rice is more responsive to N and P application as farmers of the selected locations uses the readily soluble SSP as a source of phosphatic fertilizer.…”
Section: Discussioncontrasting
confidence: 87%
“…Zinc plays an important role in nitrogen metabolism and formation of chlorophyll and carbohydrate, which leads to maintain photosynthetic activity for longer period and finally results in increasing the yield and yield attributes in pearlmillet (Mehta et al, 2008). Debnath et al 2015 find out that a conjoint dose of 60 kg phosphorus and 5 kg Zn /ha gave the highest grain yield of wheat than control and agronomic efficiency of P in basmati rice can be increased by using 40 kg phosphorus with 2.5 kg Zn/ha.…”
Section: Zinc Fertilization To Pearlmilletmentioning
confidence: 94%
“…Zinc is one of the micronutrients whose deficiency affects the crop growth and crop yield [5,8]. Zinc fertilizers are very costly and its availability is also limited.…”
Section: Zinc-solubilizing Biofertilizer (Zsb)mentioning
confidence: 99%
“…Nevertheless, the importance of fertilizers, essential for achieving increased crop production, will further increase because there is little scope for bringing more areas under cultivation and majority of soils are deficient in many macroand micronutrients. It is now realized that in agricultural lands under intensive monoculture system, including rice, which receives heavy application of chemical fertilizers alone, productivity slowly is declining, and environmental quality is deteriorating [8]. Intensification of agriculture has also widened the gap between nutrient removal and supplies and, thus, soil fertility depletion [9].…”
Section: Introductionmentioning
confidence: 99%